Acyl-ghrelin mediated lipid retention and inflammation in obesity-related Type 2 diabetes. (5th February 2019) - Churm, R.; Caplin, S.; Barry, J.; Davies, J.S.; Stephens, J.W.; Prior, S.L.
Abstract: Acyl-ghrelin has various peripheral effects including the potential role in mediating cellular lipid removal and macrophage polarization. Previous reports are contradictory as to how glycaemia and acyl-ghrelin mediates lipid retention and inflammation within individuals with Type 2 diabetes (T2D). Our aim was to explore acyl-ghrelin levels and ghrelin expression in relation to lipid and inflammatory markers within an ex vivo human model, biopsied visceral adipose tissue. Results indicated that acyl-ghrelin was associated with a decline in key lipid homeostasis genes ABCG1 and LXRβ expression. Within T2D there was also a down regulation of these genes which was independent of acyl-ghrelin levels. Circulatory pro-inflammatory markers (IL-6 and TNFα) had no association with ghrelin expression nor circulating acyl-ghrelin levels. Anti-inflammatory marker (IL-10) and total antioxidant status (TAOS%) were positively associated with ghrelin expression across samples from all groups combined (total sample cohort) and specifically within the obesity sample cohorts. Data supported the hypothesis that hyperglycaemia and acyl-ghrelin have a regulatory role in lipid retention. Furthermore, that both acyl- and desacyl-ghrelin is responsible for a protective inflammatory response; however this response is diminished in T2D. Highlights: Hyperglycaemia and acyl-ghrelin have a role in the mediation of lipid retention. Total ghrelin is responsible for a protective response to oxidative burden. Pro-inflammatory markers had no association with ghrelin. Anti-inflammatory markers are positively associated with ghrelin. Low ghrelin levels in Type 2 diabetes extinguishes associations with inflammatory health.